SIKAP ETIS POLITIS GEREJA MENYONSONG TAHUN POLITIK DI INDONESIA - Johan A Serhalawan (TANGKOLEH PUTAI, 2018)
Human beings are zoon politicians, conscious or unconscious, acknowledged or not, politics inevitably influences our lives as individuals and as part of a community group. This influence lasts from birth till death picks up man. Within twenty-four hours each day we pass, we can find many political events. The presence and involvement of the Church in politics, however, must be colored by Christian beliefs about what God's will is for the life of the nation and the state.